If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + 5 + (2x + -3) = 0 Reorder the terms: 7 + 5 + (-3 + 2x) = 0 Remove parenthesis around (-3 + 2x) 7 + 5 + -3 + 2x = 0 Combine like terms: 7 + 5 = 12 12 + -3 + 2x = 0 Combine like terms: 12 + -3 = 9 9 + 2x = 0 Solving 9 + 2x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 2x = 0 + -9 Combine like terms: 9 + -9 = 0 0 + 2x = 0 + -9 2x = 0 + -9 Combine like terms: 0 + -9 = -9 2x = -9 Divide each side by '2'. x = -4.5 Simplifying x = -4.5
| 3x+4x-9=12 | | x+6x-78=97 | | 8t^2-56t+80=0 | | 2x+4=2x+x+3 | | x-31/4=21/5 | | 2x^3+3x^3+(-6x^3)= | | 2x^2-x=100 | | (2x+110)+2x=300 | | 1/2y≤-7 | | 10x^3-1250=0 | | (x-4)(x-3)(x-2+3i)(x+2+3i)=0 | | 2(2x+110)+2x=300 | | 2(x+3)+5x= | | 2y=-7x+12 | | (2x+17)=(8x-13) | | X^3-8x^2=-12x | | 11n-6-10n-1=8 | | (X+5)=14 | | 6x-2x-25=31 | | 6x-2x-25=32 | | d/3-10=2 | | x^2+9x-54=0equation | | 231=-7(-4n-1) | | 2y-20=180 | | K+14=19 | | 2x-6=10.5 | | (3x-2)(x-8)=0 | | k/7=9/7 | | 6m+19=7m+9 | | -1/4y-16 | | 4x^2+24=20x | | 6y=-2x+12 |